BUDAYA PELA GANDONG SEBAGAI STRATEGI KOMUNIKASI KRISIS PENYELESAIAN KONFLIK AMBON - JODI SALAHUDIN; DIAN NATALIA SEPTORY; MARTHEN JAR ARPIPI; YOEL UKWATU; ALENTINA DARKHU (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
The Ambon conflict is one of the most terrible social conflicts that has ever occurred in Indonesia. Conflict in 1999, and left more than 5,000 people dead and tens of thousands displaced. Resolving the Ambon conflict is a very difficult task. Resolving this conflict not only requires efforts from the government, but also from the Maluku people themselves. One effort that can be made to resolve the Ambon conflict is through a crisis communication strategy. Crisis communication strategies are efforts to manage communication in crisis situations. Crisis communication is important in conflict resolution. Crisis communications can be used to build trust, reduce tensions, and encourage dialogue. Pela Gandong culture is a culture that can be used as a crisis communication strategy in resolving the Ambon conflict. Pela Culture This research uses qualitative methods with a case study approach. Research data was collected through in-depth interviews, observation and documentation. The research results show that Pela Gandong culture can be used as a crisis communication strategy in resolving the Ambon conflict. Pela Gandong culture can be used to build trust, reduce tension, and encourage dialogue. This research provides input for the government and people of Maluku in efforts to resolve the Ambon conflict. The government and people of Maluku can use Pela Gandong culture as a crisis communication strategy in resolving the Ambon conflict.